Bacteria That Cause Enteric Diseases Stimulate Distinct Humoral Immune Responses - Amadou Amani, Souwelimatou; Lang, Mark L. (Frontiers in Immunology, 2020)
Bacterial enteric pathogens individually and collectively represent a serious global health burden. Humoral immune responses following natural or experimentally-induced infection are broadly appreciated to contribute to pathogen clearance and prevention of disease recurrence. Herein, we have compared observations on humoral immune mechanisms following infection with Citrobacter rodentium, the model for enteropathogenic Escherichia coli, Vibrio cholerae, Shigella species, Salmonella enterica species, and Clostridioides difficile. A comparison of what is known about the humoral immune responses to these pathogens reveals considerable variance in specific features of humoral immunity including establishment of high affinity, IgG class-switched memory B cell and long-lived plasma cell compartments. This article suggests that such variance could be contributory to persistent and recurrent disease.